Near-inertial waves generated by typhoon MITAG under the influence of anticyclonic eddy east of Taiwan - Zheng, Tongtong; Yu, Fei; Ren, Qiang; Nan, Feng; Chen, Zifei; Liu, Yansong; Hu, Yibo; Ding, Ya-nan (Frontiers in Marine Science, 2023)
Based on subsurface mooring observations and HYCOM data, a complete investigation was conducted of the near-inertial waves (NIWs) caused by Typhoon MITAG to the east of Taiwan. HYCOM data were mainly used to reveal the role played by anticyclonic eddies in the propagation of NIWs. The results show that most typhoon-generated NIWs propagate towards negative vorticity, and NIWs near the edge gradually accumulated towards the eddy center and down to 800 m. NIWs propagating through the thermocline to the deep ocean were mainly concentrated in the eddy, and the near-inertial energy flux showed a significant enhancement from 400 to 600 m. Moreover, the downwards propagation of NIWs in the eddy enhanced the kinetic energy of background flow. NIWs outside the anticyclonic eddy dissipated quickly, while inside the eddy, there were high value areas of e-folding time. Dynamic mode decomposition illustrates that the anticyclonic eddy mainly captures higher modes of NIWs, and the state of continuous energy growth of higher modes can be maintained for more than a week. In addition, NIWs can also be carried westwards by the advection of the mean background flow at the eddy’s edge.